Pelaksanaan Peraturan Daerah Provinsi Bali Nomor 3 Tahun 2018 Tentang Retribusi Jasa Usaha pada Objek Wisata Monumen Perjuangan Rakyat Bali - Ni Kadek Yunika Pramesti; I Nyoman Putu Budiartha; Luh Putu Suryani (Jurnal Analogi Hukum, 2022)
Where the government has more control and control over its territory, including the authority to regulate finances in carrying out obligations and functions such as development activities and services. authority. including the authority to regulate finances in carrying out their duties and functions. The purpose of this study was to determine the effectiveness of the enactment of local regulations on the Bali People's Struggle Monument tourism to increase regional income and to find out the obstacles in its implementation. This study uses empirical legal research methods with a sociological approach. The results of this study indicate that the contribution of the levy on the Bali People's Struggle Monument to the Bali Province's original revenue is relatively small. Obstacles in implementing the Bali Provincial Regulation Number 3 of 2018 concerning Business Service Retribution are divided into two, namely external constraints such as lack of awareness of mandatory levies in paying user fees and internal constraints such as the lack of human resources and lack of funds for monument maintenance. Several forms of efforts were made to overcome the obstacles, namely by providing socialisation to the retribution obligors about the importance of carrying out the obligation to pay retribution.